Pygopus 2 promotes kidney cancer OS-RC-2 cells proliferation and invasion in vitro and in vivo - Rongfu Liu; Xiangcheng Qin; Chengyong Ji; Weixin Zeng; Yufeng Yang; Wei Tan (Asian Journal of Urology)
Objective: Human Pygopus 2 (Pygo2) was recently discovered to be a component of the Wnt signaling pathway required for β-catenin/Tcf-mediated transcription. But the role of Pygo2 in malignant cell proliferation and invasion has not yet been determined. Methods: Lentivirus-mediated small interfering RNA (siRNA) and vector-based overexpression were used to study the function of Pygo2 in OS-RC-2 cells. The resulted cells were subject to Western blotting assay, MTT assay, colony formation and cell invasion assays. Furthermore, renal cell carcinoma (RCC) models were established in BALB/c nude mice inoculated with OS-RC-2 cells. Immunohistochemistry (IHC) staining of matrix metalloproteinase-7 (MMP-7), matrix metalloproteinase-9 (MMP-9) and vascular endothelial growth factor (VEGF) was performed in tumor tissue. Results: Pygo2 gene was successful knocked down and overexpressed in RCC OS-RC-2 cells by using an shRNA and overexpressing vector, respectively. Overexpression of Pygo2 effectively promoted cell proliferation, colony formation and invasion in vitro. Knockdown of Pygo2 obviously inhibited xenograft tumor growth in nude mice. In addition, overexpression of Pygo2 increased the levels of MMP-7, MMP-9 and VEGF in the xenograft tumors. Conclusion: Pygo2 has a role in promoting cell proliferation, invasion and metastasis, and may regulate angiogenesis via the Wnt/β-catenin signaling pathway.